Metagenomic analysis between free-living and cultured Epinephelus fuscoguttatus under different environmental conditions in Indonesian waters. Issue 2 (30th September 2016) - Hennersdorf, Philipp; Mrotzek, Grit; Abdul-Aziz, Muslihudeen A.; Saluz, Hans Peter
Abstract: In this study, we analyzed and compared feces of free-living and cultivated fish species, Epinephelus fuscoguttatus under different environmental conditions in Indonesian waters. Metagenome analysis was performed using Illumina MiSeq sequencing of the whole metagenomic DNA isolated from fish feces samples. The analysis covered both prokaryotic and eukaryotic DNA. Feces samples from mariculture fish revealed a highly stable distribution of several orders of bacteria when compared to samples from free-living fish, which were highly diverse and dominated by Vibrionales, Pseudomonales, Rhizobiales and non-classifiable Alphaproteobacteria . The eukaryotic content of the samples was dominated by residues of the host and nine additional fish species that formed a portion of the diet. Investigations on functional annotations for predominant bacterial taxa, using Gene Ontology enrichment, revealed a number of functions related to DNA metabolic processes, especially DNA repair, as well as antibiotic response in the free-living fish species. Highlights: Metagenomics of Indonesian fish feces under different environmental conditions Metagenomics were performed by MiSeq of the total DNA isolated from samples. The analysis comprised both prokaryotic and eukaryotic organisms. Metagenomics revealed information on food and biological functions.